Functional Outcomes and Complication Analysis of Plate Osteosynthesis versus Hemiarthroplasty in Three-part and Four-part Proximal Humerus Fractures - Baris Peker; Ayse Esin Polat; Engin Carkci; Ahmet Senel; Cenk Soydan; Tolga Tuzuner (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the functional results and complications of open reduction-internal fixation and hemiarthroplasty performed in Neer three-part and four-part proximal humerus fractures. Methods: The retrospective study was conducted at the Istanbul Training and Research Hospital, Turkey, and comprised data of patients who were diagnosed with three-part or four-part fracture of the proximal humerus and underwent surgical procedure between January 2008 and April 2013. Those who had undergone open reduction-internal fixation using anatomical locking plates were placed in group A, and those who had undergone hemiarthroplasty were in group B. Constant-Murley shoulder outcome, University of California at Los Angeles shoulder and visual analogue scale scores were compared between the two groups. The degrees of forward flexion and abduction of the glenohumeral joint were recorded. Complications in both the groups were recorded. Data was analysed using SPSS 15. Results: Of the 48 patients, 30(62.5%) were in group A; 16(53.3%)males and 14(46.7%) females, with an overall mean age of 60.0±9.4 years. The remaining 18(37.5%) were in group B; 7(39%) males and 11(61%) females, with an overall mean age of 67.3±10.1 years. The mean follow-up period was 18.7±16.4 months. The mean Constant-Murley and University of California at Los Angeles shoulder scores were not significantly different between the two groups (p>0.05). The mean visual analogue scale score was significantly higher in group A compared to group B (p=0.021). Continuous...